Factors Associated with Stunting in Toddlers in The Ropang District of Sumbawa - Lestari, Ana; Wahyu Tarikawati, Atri; Yuliastuti, Luh Putu Sri (VISIKES, 2025)
Stunting is a critical public health issue that impairs physical and cognitive development in children, particularly in underserved areas. This study aimed to analyze the relationship between parental nutritional knowledge, parenting practices, and feeding patterns with the stunting status of children under five in Ropang Subdistrict, Sumbawa. A cross-sectional design was used, and total sampling was applied to 24 respondents including 12 respondents of mother and 12 respondents of toddlers. This study used a small sample size because it focused on children who were already classified as stunted. Data were collected through structured questionnaires and analyzed using the chi-square test, Likelihood Ratio, and Fisher’s Exact Test. The results showed no significant relationship between parents’ nutritional knowledge and the stunting status of children (p = 0.310). However, there was a significant relationship between parenting practices and stunting (p = 0.023), as well as a very strong association between child feeding patterns and stunting status (p < 0.001). Children with poor feeding patterns were more likely to experience severe stunting. These findings emphasize the importance of practical parenting strategies and proper feeding behavior in addressing stunting. Effective interventions should therefore focus on improving daily caregiving and feeding practices, rather than relying solely on increasing parental knowledge, to enhance child health outcomes in rural communities.